PENGARUH PELAYANAN, IKLAN DAN PUBLISITAS TERHADAP KEPUTUSAN NASABAH DALAM MENABUNG DI BANK BRI SYARIAH - Shelly Midesia; Siti Fatimah; Fahriansah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to determine the effect of service, advertising, and publicity on customer decisions in saving at BRI Syariah Bank. The sampling method in this study using random sampling with a total sample of 100 customers of Bank BRI Syariah Stabat Langkat Regency. The data analysis method used is multiple linear regression analysis. The results of the partially tested research show that service and advertising have a significant effect on customer decisions to save at BRI Syariah Bank, while publicity has no significant effect on customer decisions in saving at BRI Syariah Bank. Simultaneous testing shows that service, advertising, and publicity have a significant effect on customer decisions in saving at BRI Syariah Bank